Efficacy of heat mitigation strategies on core temperature and endurance exercise: A meta-analysis - Badriyah Alhadad, S.; Tan, P. M. S.; Lee, J. K. W. (Frontiers in Physiology, 2019)
Background: A majority of high profile international sporting events, including the coming 2020 Tokyo Olympics, are held in warm and humid conditions. When exercising in the heat, the rapid rise of body core temperature (Tc) often results in an impairment of exercise capacity and performance. As such, heat mitigation strategies such as aerobic fitness (AF), heat acclimation/acclimatization (HA), pre-exercise cooling (PC) and fluid ingestion (FI) can be introduced to counteract the debilitating effects of heat strain. We performed a meta-analysis to evaluate the effectiveness of these mitigation strategies using magnitude-based inferences.